PERANCANGAN PONDOK PESANTREN TAHFIDZUL QUR’AN AL-MUTTAQIIN TAKI NIODE DENGAN PENDEKATAN ARSITEKTUR ISLAM - Adam, Dhea reza; Haisah, S.; Tamrin, Moh. Muhrim (Venustas, 2023)
This design aims to 1) know the macro and micro concepts in designing the Tahfidzul Qur'an Islamic Boarding School in Gorontalo Province, 2) to know the design and application in terms of structure and arrangement using Islamic Architecture, 3) to materialize the Tahfidzul Qur'an Islamic Boarding School building which has adequate and proper facilities. The data collection method employed in this design is observation, namely observing internal and external conditions through secondary data collection, namely by conducting literature studies and documents as support to the design. This design is located in a strategic area that is in following the Regional Spatial Plans of Bone Bolango District in Gorontalo Province.